News as a Means of Popularization of First Aid Knowledge: Content Analysis of News Articles Related to Cases of Pediatric Cardiac Arrest in Schools and Kindergartens of Russia - A. A. Birkun; S. A. Samarin; A. A. Tupotilova (Неотложная медицинская помощь)
RELEVANCE In Russia, insufficient motivation and low readiness of laypeople to provide first aid (FA) stipulate low rates of bystander cardiopulmonary resuscitation (CPR) and, as consequence, high mortality from cardiac arrest (CA). News reports on real cases of CA, in addition to describing circumstances of the event, may carry important information promoting FA provision among a wide audience. However, existing practice of presenting such content in Russian media sphere is unknown.AIM To investigate contemporary trends for presentation of information on the problem of CA and provision of help in CA in reports of online news media on the example of a news sample about cases of pediatric CA in kindergartens and schools of Russia.MATERIAL AND METHODS In August 2021, Google and Yandex were searched for Russian-language news reports describing cases of CA that happened in children in Russian schools and kindergartens in 2020, and structured content analysis of the news was carried out.RESULTS The study sample consisted of 207 news reports describing 21 unique case of CA. In 76.2% cases (n=16) CA occurred in children at school, in 23.8% cases (5) — at kindergarten. At least in 28.6% of cases (6) Emergency Medical Services providers did not attempt CPR at arrival on scene. FA provision by bystanders was described in two cases (9.5%), provision of help by medical employees of educational organizations — in six cases (28.6%). Only in one case (4.8%) the child was transferred to a hospital after successful resuscitation. In the rest of cases (n=20; 95.2%) biological death was verified on scene. Information on the value of FA for saving life in CA was present in one out of 207 news reports (0.5%); and there were no reports mentioning legal aspects of FA provision, describing procedure of FA in CA, or highlighting the importance of mass public resuscitation education.CONCLUSIONS News reports that describe cases of CA confirm high relevance of the problem, but do not carry important information related to popularization of FA knowledge. Inclusion of information on significance, principles and procedures of providing FA to CA victims into the content of the news reports is necessary for establishing positive public opinion and increasing motivation of the general population of Russia towards training in FA and FA provision. This in turn indicates the necessity for enhancing awareness of the professional journalistic community on the problem of FA provision in CA.